PENERAPAN RESTORATIVE JUSTICE TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA ASUSILA (Study Kasus Putusan Pengadilan Negeri Mempawah Nomor : 2/Pid.Sus-Anak/2015/PN. Mpw) - LANORA SIREGAR, SH NIM. A.2021131063, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
HumSahata Simamora, SH., MHABSTRACTThis thesis discusses the application of restorative justice against children as a criminal immoral (Study Mempawah District Court Nomor 2/Pid.Sus-Anak/2015/PN. MPW). The method used in this research is normative and empirical legal approach. From the results of this thesis can be concluded that the effectiveness of restorative justice against children as a criminal Mempawah sacrilegious in the District Court relating to Decision Nomor 2/Pid.Sus-Anak/2015/PN. MPW that the judge did not give Restorative Justice diversion of children who commit criminal acts immoral, seen in the judge's ruling the judge only institute and pay attention to article 3 of the Criminal Code perma No. 4 of 2014 on guidelines for the implementation of diversion in the juvenile criminal justice system. In a copy of the judge's decision not to consider laws - laws protecting children, the criminal justice system of children and perma article 2 before article 3 that is known in this article provides an opportunity for victims and perpetrators to resolve this criminal act by consensus as contained in the perma number 4 in 2014. that some limiting factor in the implementation of restorative justice as an alternative implementation of the punishment against children in conflict with the law, among others, are still very limited physical aspect of the building where the implementation of restorative justice, as well as non-physical, namely the unavailability of trained professionals such as doctors, psychologists, energy skills instructors and educators in various places where children were placed during the handling of legal proceedings. Factors legal substance, as a model of restorative justicehas not been explicitly prescribed in the legislation, although in Law No. 11 of 2012 on the Criminal Justice System Child has arranged but until now has not been declared valid. Factor structure of the law, the implementation of the application of restorative justice as an alternative in the execution of punishment on children in conflict with the law attributable to the number of law enforcement officers from the level of the investigation, to the execution of court decisions held at the Correctional Institution is still a deep understanding of the concept of restorative justice as a settlement in the treatment of children in conflict with the law, which is still limited understanding of who owned the sense semantically or language, so that the principles and values contained in the restorative justice is still less they understand. Factors still attached to the paradox of a culture of people who think that every crime should be rewarded with imprisonment / punishment and will not make again behavior forgive the perpetrator by the victim associated with the suffering experienced by the victims of the crimes committed by the offender, and the absence of sanctions for law enforcement agencies that do not implement restorative justice and diversion in the treatment of children in conflict with the law although it is set in the legislation.Keywords: Application, Restorative Justice, Against Children, As an Actor, Crime immoral.